The Complete List of Solutions to Möbius's Exponential Equation (European Journal of Pure and Applied Mathematics, 2025)
Möbius addition is a non-associative binary operation defined on the complex open unit disk $\mathbb{D} = \{z\in\mathbb{C}:|z|
Keywords: Mobius addition; Mobius's Exponential Equation; associator function; gyrogroup; non-linear equation